2020
DOI: 10.17826/cumj.723669
|View full text |Cite
|
Sign up to set email alerts
|

Determination of risk factors affecting fear of childbirth during pregnancy

Abstract: We aimed to investigate the level of fear of childbirth in pregnant women in terms of factors such as age, number of births, education level, and immigration status. Materials and Methods: This cross-sectional study was carried out by including 444 pregnant women who have 32-36 weeks of pregnancy and voluntarily agree to participate in the research, all of them are literate and applied to Kütahya Health Sciences University Evliya Çelebi Training and Research Hospital between 25.07.2019 -01.11.2019. The data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In our current study conducted with the same scale, fear of childbirth increased with education level, but according to the study conducted before the pandemic period, it was seen that the fear of childbirth scores did not increase statistically at all education levels during the pandemic period. In studies conducted before the pandemic in Turkey, the mean fear of childbirth score was lower than during the pandemic period 17 , 26 , 27 .…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…In our current study conducted with the same scale, fear of childbirth increased with education level, but according to the study conducted before the pandemic period, it was seen that the fear of childbirth scores did not increase statistically at all education levels during the pandemic period. In studies conducted before the pandemic in Turkey, the mean fear of childbirth score was lower than during the pandemic period 17 , 26 , 27 .…”
Section: Discussionmentioning
confidence: 77%
“…For this reason, health professionals should question the psychological status of patients related to anxieties during pregnancy follow-up and ensure that they receive psychiatric help when necessary. The study we conducted before the pandemic showed that as the education level increases, the fear of childbirth scores, as measured by the WDEQ-A score, also increase 17 . In our current study conducted with the same scale, fear of childbirth increased with education level, but according to the study conducted before the pandemic period, it was seen that the fear of childbirth scores did not increase statistically at all education levels during the pandemic period.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation